1999
DOI: 10.1136/bjo.83.3.358
|View full text |Cite
|
Sign up to set email alerts
|

Early drusen formation in the normal and aging eye and their relation to age related maculopathy: a clinicopathological study

Abstract: Aim-To describe the early formation of drusen and their relation to normal aging changes at the macula and to the development of age related maculopathy (ARM). Method-Histopathological features of 353 eyes without histological evidence of ARM are described and correlated with the clinical appearance. In addition, 45 of these eyes were examined by transmission electron microscopy. Results-Drusen were detected histopathologically in 177 (50%) eyes but were seen clinically in only 34% of these. Drusen were mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
186
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(203 citation statements)
references
References 22 publications
7
186
0
6
Order By: Relevance
“…In another study, Pauleikhoff et al (1990) indicated the appearance of small membrane-bound vesicles and membrane fragments. Other studies also reported membranous debris (Curcio and Millican 1999;Curcio et al, 2005a), long spacing collagens (Sarks, 1976;van der Schaft et al, 1991), drusen (Green and Enger, 1993;Sarks et al, 1999;Hageman and Mullins, 1999)), and fine granules in BrM (Killingsworth, 1987;Curcio and Millican 1999). In our studies, we found three types of inclusions in QFDE images: LLPs, SGs, and membrane-like structures.…”
Section: Inclusions Found In Brmsupporting
confidence: 64%
See 3 more Smart Citations
“…In another study, Pauleikhoff et al (1990) indicated the appearance of small membrane-bound vesicles and membrane fragments. Other studies also reported membranous debris (Curcio and Millican 1999;Curcio et al, 2005a), long spacing collagens (Sarks, 1976;van der Schaft et al, 1991), drusen (Green and Enger, 1993;Sarks et al, 1999;Hageman and Mullins, 1999)), and fine granules in BrM (Killingsworth, 1987;Curcio and Millican 1999). In our studies, we found three types of inclusions in QFDE images: LLPs, SGs, and membrane-like structures.…”
Section: Inclusions Found In Brmsupporting
confidence: 64%
“…As only one drusenoid structure was observed in QFDE preparation of our study, its morphological features could not represent all types of drusen described in other studies (Green et al, 1985;Green and Enger, 1993;Sarks et al, 1999;Hageman and Mullins, 1999). Nevertheless it fits the characteristics of "entrapment site", a phenotype of CMBBs described in eyes with clinically undetectable drusen (Sarks et al, 1999).…”
Section: Inclusions Found In Brmmentioning
confidence: 47%
See 2 more Smart Citations
“…Time-dependent lipofuscin accumulation in retinal pigment epithelial (RPE) cells has been notoriously deemed as a major risk factor in association with age-related macular degeneration (AMD) (Bressler et al, 1988;Eldred and Katz, 1988;Eldred and Lasky, 1993;Kliffen et al, 1997;Sarks et al, 1999;Delori et al, 2000). AMD, the leading cause of blindness in elderly people, is a degenerative disease of the eye (Bressler et al, 1988;Mata et al, 2000;Telander, 2011), for which there is thus far no remedy.…”
Section: Introductionmentioning
confidence: 99%